Leading from a feminist soul - Hackney, Catherine E. (Emerald Publishing Limited : Information Age Publishing, Inc, 2019)
Most of the literature involving the work of women leaders has addressed barriers that historically have required women to struggle to "get to the top," the "styles" of women leaders, and gender issues women leaders continue to face in society and the workplace. Nearly missing in the literature is the perspective that women who possess positional power also have a responsibility to make a positive, constructive difference with that power. Though many women have made that kind of a difference, the purpose of this book is to prompt other women leaders to ask themselves the question: "So, how does my leading make a positive difference to my organization, to my society, to my world?"This book will offer inspiration, guidance, and affirmation to women who seek to lead from goodness, justice, and the power of difference they bring to the organization.The book will include references to the authors' autobiographical experiences as leaders in K-12 and higher education as well as to women whose stories of leadership are of particular interest: an artist, a philanthropist, a community activist, teacher and school leadership educators. These references will scaffold the construction of a theory of leadership that circles around awareness of self and others, and the social consciousness, courage, humility, and generosity of spirit that is characteristic of leading from the feminist soul.